OphthoEvidence report: Comparative effects of prophylactic strategies for post-intravitreal injection endophthalmitis: Protocol for a systematic review and network meta-analysis - Maryam Ghadimi; Dena Zeraatkar; João Pedro Lima; Jinhui Ma; Sunir Garg; Peter Kaiser; David Steel; Tien Yin Wong; Sobha Sivaprasad; Charles Wykoff; Varun Chaudhary (PLoS ONE, 2026)
Background Endophthalmitis is a rare but serious complication of intravitreal injections (IVI). To mitigate the risk of post-injection endophthalmitis (PIE), retinal specialists use different strategies, combining various prophylactic measures. However, existing systematic reviews have evaluated the effects of these measures in isolation, which does not consider their concurrent use in practice. A trustworthy systematic review with network meta-analysis (NMA) by providing a framework for simultaneous comparisons of different prophylactic combinations is essential to guide decision-making. Objectives To present a protocol for addressing the comparative effects of different strategies for the prevention of PIE. Methods We will search Medline, EMBASE, Cochrane CENTRAL, Web of Science, and ClinicalTrials.gov from inception for randomized controlled trials and observational studies comparing any strategy for preventing PIE with an alternative strategy, or placebo, or no prophylactic strategy in patients aged 18 years or older who received IVI of any pharmacological agent for any indication except treatment of bacterial endophthalmitis. Paired reviewers will independently screen studies, extract the data and assess risk of bias for each outcome that includes infectious endophthalmitis, confirmed endophthalmitis, any endophthalmitis, need for surgical intervention for management of PIE, and best-corrected visual acuity. For each outcome, when possible, we will conduct frequentist random-effects NMAs. We will assess the certainty of evidence and interpret findings using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Discussion This systematic review and NMA will provide a comprehensive and up-to-date summary of the evidence addressing the effects of all available strategies for the prevention of PIE. Registration Open Science Framework ( https://doi.org/10.17605/OSF.IO/SJC4U ).